2003
DOI: 10.1063/1.1589473
|View full text |Cite
|
Sign up to set email alerts
|

The role of phase in molecular Rydberg wave packet dynamics

Abstract: The dynamics of Rydberg wave packets in NO are investigated in the regime where the electronic period is comparable with the rotational motion of the molecular ion core. The presence of a rotating molecular core manifests itself in the wave packet dynamics as a series of peaks separated by the rotational beat period T Rot , but offset by ⌬T Rot , where ⌬ is the difference in quantum defect between the two dominant Rydberg series in the superposition. We rationalize this by treating the dynamics of a wave packe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Part of this complexity comes from the many interacting states that lie extremely close in energy. An alternative route to understanding these systems is through the study of their dynamics using time resolved spectroscopy methods [5,6], generally requiring femtosecond to picosecond pulses of laser radiation. Since the maximum photon energy available in a conventional femtosecond laser system is limited to ∼6 eV, excitation of highly excited electronic states requires the use of multiphoton excitation schemes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Part of this complexity comes from the many interacting states that lie extremely close in energy. An alternative route to understanding these systems is through the study of their dynamics using time resolved spectroscopy methods [5,6], generally requiring femtosecond to picosecond pulses of laser radiation. Since the maximum photon energy available in a conventional femtosecond laser system is limited to ∼6 eV, excitation of highly excited electronic states requires the use of multiphoton excitation schemes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…2(a) shows the experimental recurrence spectrum following excitation of a single wave packet. The first recurrence exhibits the double peak structure that has been observed in previous experiments [15]. The dip corresponds to destructive interference between the two wave packets when they return to the core with an accumulated phase difference of , and is observed at time t ave .…”
mentioning
confidence: 68%
“…When both wave packets return to the core and overlap spatially (i.e., t t a cl t b cl , which is true for 2 2 a E rot 1) they will interfere with one another, and Eq. (1) can be rearranged to give the stroboscopic periods T s T rot k for 2 k [15]. These interference effects have been observed in time-resolved spectra of molecular Rydberg wave packets in NO, manifesting themselves as plateaus in plots of the observed recurrence time as a function of the average principal quantum number in the superposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our own group, we have studied the intermediate Rydberg states of NO, with principal quantum number n = 25-35 in static and ramped external fields [32][33][34]. We have also investigated the dynamics of Rydberg electron wave packets in NO [35][36][37] and demonstrated that it is possible to control the composition of the wave packet by employing phase-locked pairs of optical pulses [1,2].…”
Section: Introductionmentioning
confidence: 99%